HEAT AND MASS TRANSFER DURING AIR DRYING OF SWEET POTATO - Manal H. AL-Hafidh (Journal of Engineering, 2009)
This study included the convective air drying of a single sweet potato sample which is taken as an ellipsoid with (40mm) in the longitudinal direction and (20mm) in the thickness direction. Convective heat and mass transfer takes place between the sample surface and its drying environment; while, unsteady heat conduction and moisture diffusion take place within the drying body without phase change for liquid (evaporation occurs at the surface only). The numerical solution of the mass, energy conservation equations was used; by applying the finite difference technique after using the body fitted coordinate system with grid generation techniques. A set of empirical correlations have been employed to determine the product properties and the important affecting factors on the drying process were studied. The results showed that the product temperature is increased and its moisture content is decreased with time and the increase in air velocity caused an increase in the heat transfer coefficient and as a result moisture content will decrease and this accelerates the drying process. The numerical results were compared with experimental results and showed good agreement.